Barriers and suggestions towards deceased organ donation in a government tertiary care teaching hospital: Qualitative study using socio-ecological model framework - Britzer Paul Vincent; Gunjan Kumar; Sreejith Parameswaran; Sitanshu Sekar Kar (Indian Journal of Transplantation, 2019)
Background: Although the science of transplant has grown, its complementary field “organ donation” is still in its infancy stage in India. There have been very few center-based studies to understand the barriers toward organ donation in a government hospital. Moreover, all of those few studies were from an objectivist point of view and were not subjectivist in approach. Aim: Therefore, this study aims to understand the subjective views on barriers in the process of deceased organ donation among the stakeholders and their suggestions to improve in a government hospital's transplant unit. Methods: Qualitative (subjectivist) method was undertaken to attain the aim of the study and was analyzed using the socio-ecological model (SEM). In-depth interviews were carried out with stakeholders such as nephrologist, urologist, transplant coordinator, a transplant nurse, donor family, and an organ recipient. Results: Each level of the SEM played a vital role in the process of organ donation and they were interwoven with each other. The barriers toward the process of deceased organ donation were mistrust on the health care, unknown will of the deceased, poor communication, interfering of untrained professionals during grief counseling, family background, and lack of incentives and support toward the deceased organ donation program from the administrators. Conclusion: It is worthy to consider the process of organ donation from a Multi-disciplinary viewpoint in planning for future policies, interventions, and research. It is essential to conduct qualitative research to understand more about the barriers toward the practice of organ donation from the service receiver's and provider's perspective.